2001
DOI: 10.1002/ajim.1033
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, lung function and cell surface markers in a group of hemp fiber processors*

Abstract: Lung function changes and abnormalities in a profile of cell surface activation markers and antibodies were noted to relate to the presence of work-related respiratory symptoms, not seen in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Occupational exposure to organic dust has been particularly problematic in the hemp processing industry and is a risk factor for the development of work-related respiratory symptoms. (3, 57) Although bacteria and fungi were not quantified in the present study, the sequence data provide preliminary insight to suggest that workers undertaking various occupational tasks could be exposed to a variety of microbial hazards.…”
Section: Discussionmentioning
confidence: 72%
“…Occupational exposure to organic dust has been particularly problematic in the hemp processing industry and is a risk factor for the development of work-related respiratory symptoms. (3, 57) Although bacteria and fungi were not quantified in the present study, the sequence data provide preliminary insight to suggest that workers undertaking various occupational tasks could be exposed to a variety of microbial hazards.…”
Section: Discussionmentioning
confidence: 72%
“…26 Studies of PM concentrations during hemp manufacturing noted high personal exposure levels ranging from 10.4 to 79.8 mg/m 3 . 27 In contrast, the few studies that measured organic dust in medicinal and recreational cannabis facilities have reported lower exposures on the order of 0.01 to 20.5 mg/m 3 . 28 29 While these concentrations mostly fell below regulatory limits, they varied significantly according to task, with highest levels observed during grinding and sifting of dried plant product.…”
Section: Inhalational Exposures Associated With Cannabis Productionmentioning
confidence: 97%
“…Reviews suggested that workers at Cannabis cultivation facilities (CCFs) are exposed to organic dust (molds, pollens, bacteria, other allergens, and bioaerosols), VOCs, fungicides, and pesticides . An interview of Cannabis cultivation facilities (CCFs) workers found that 71% presented some work-related symptoms, and the majority of symptoms (65%) was respiratory (76)(77)(78)(79)(80). Workers in indoor cultivation of Cannabis are mostly in contact with "raw" material, whereas consumers are exposed to processed or combusted material (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80).…”
Section: Volatile Organic Compounds (Vocs) : Adverse Health Effectsmentioning
confidence: 99%